Guidelines for Development of Qualiy Village Health Volunteers (VHVs) to Support the Health Workforce for the Future Health System - เทียนจารุวัฒนา วิเชียร; เนาว์สุวรรณ กิตติพร; วชิระประพันธ์ สายสมร (Journal of Health Science of Thailand, 2021)
The objective of this study was to produce a guideline for the devlopment of qualiy village health volunteers (VHVs) together with a quality assessment tool. Two study methods were applied: (1) quantitative method to collect opinions on the quality of VHVs among 31,883 VHVs selected through random sampling from the total VHV population; and (2) the qualitative method to obtain suggestions on the characteristics of a quality VHV from 22 head or sub-head of VHVs purposively selected. Quantitative data were collected by online survey using a newly created questionnaire, of which the content validity was checked and obtained IOC ranged 0.67-1.00. The data were analyzed by using descriptive statistics. For the qualitative study, data collection was conducted via telephone interviews using a semi-structured questionnaire. The study found that majority of VHVs agreed that desirable qualifications of VHVs should cover 4 dimensions of attitude, knowledge, skills, and behavioral expression. For the attitude, a quanlity VHV should have volunteer spirit and being supportive to community needs. The knowledge dimensions should cover basic public health for caring people of all age groups, community development, and communication technology. For the skills dimension, 3 components were essential: health care, specialized and specific skills. On the behavioral expression, it covered 6 areas which included the practice based in norms, being a role model in self-care, applying integrated care for all ages, taking care people’s mind, promoting quality of life, and implementing the health policies. The results of this study could be applied as a guideline for an assessment of quality VHVs taking into account different local context. As for the quality assessment, it could be performed comprehensively by self assessment, by supervisers, and by people recieving their services; and the decision should be made by a specific committee. In conclusion, the development of quality VHVs should cover all essential dimensions so that the VHVs would be able to support the health personnel for effectively solving health problems in their area.